Role of Subthreshold Diode Laser in Cases of Diabetic Macular Edema - Abidin, Ali Zain Ul; Rehman, Munib Ur; Qureshi, Iqra (Biological and Clinical Sciences Research Journal, 2026)
Diabetic macular edema is a major cause of visual impairment among patients with diabetic retinopathy. A subthreshold diode laser is a retinal-sparing treatment option that may reduce macular thickness and improve vision without causing visible retinal damage. Objective: To evaluate the anatomical and functional outcomes of subthreshold diode laser in patients with diabetic macular edema. Methods: This prospective interventional study was conducted at the Ophthalmology Department of a tertiary care hospital from July 2025 to December 2025. A total of 70 patients with diabetic macular edema were enrolled through non-probability consecutive sampling. Patients aged 30–75 years with best-corrected visual acuity between 0.2 and 1.0 logMAR and central macular thickness between 300 and 500 µm were included. All patients underwent baseline ophthalmic evaluation, optical coherence tomography assessment, and standardized subthreshold diode laser treatment. Follow-up was performed at 1, 3, and 6 months. The primary outcome was change in central macular thickness at 6 months, while secondary outcomes included change in visual acuity, anatomical response, rescue anti-VEGF requirement, and adverse events. Data were analyzed using SPSS version 26. Results: The mean age of the patients was 55.6 ± 8.9 years, and 40 (57.1%) were male. Mean central macular thickness decreased significantly from 386.4 ± 54.2 µm at baseline to 312.9 ± 38.5 µm at 6 months, with a mean reduction of 73.5 ± 41.6 µm (p<0.001). Mean best-corrected visual acuity improved from 0.53 ± 0.20 logMAR to 0.40 ± 0.17 logMAR (p<0.001), while ETDRS letter score improved from 58.2 ± 10.4 to 64.9 ± 9.2 letters (p<0.001). Complete anatomical response was achieved in 24 (34.3%) eyes and partial response in 35 (50.0%) eyes. Rescue anti-VEGF therapy was required in 8 (11.4%) eyes. No clinically visible laser scar, choroidal neovascularization, subretinal hemorrhage, or treatment-related retinal atrophy was observed. Favorable response was significantly associated with shorter duration of edema, baseline central macular thickness <400 µm, and HbA1c ≤8%. Conclusion: Subthreshold diode laser was associated with significant improvement in visual acuity and central macular thickness in selected patients with diabetic macular edema. The treatment showed a favorable safety profile, with no serious laser-related ocular complications. It may be a useful option for patients with mild to moderate edema, shorter disease duration, and better glycemic control.